ENGLISH TEACHERS’ INSIGHT OF WRITING TEACHING MODULE IN PHASE D AT “MERDEKA” CURRICULUM - Yunik Susanti; Diani Nurhajati; Dewi Kencanawati; Rika Riwayatiningsih; Firda Anisa Sukmayani; Nike Aprilia (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The implementation of “Merdeka” curriculum continues to be carried out at all levels of education in Indonesia with the aim of improving teaching learning process. This policy certainly brings impacts and changes for teachers and stakeholders of Indonesian education. One of the changes is about planning the lesson. In this new curriculum, teachers need to have a lesson plan or teaching module to help direct the learning process to achieve learning outcomes that have been stated by the government. This case study aims to investigate teachers’ understanding toward the preparation of teaching module, especially English subject in phase D. Twenty-seven Junior High School English teachers in Kediri became the subjects of this study. The data were collected through a closed-ended questionnaire with five answer choice options submitted online through the Google Form application followed by a guided- interviews. The results showed that in general teachers had good understanding of Phase D English learning outcomes, components of teaching modules and their development, English learning approaches using the Genre Based Approach and its cycles and stages. However, some of teachers were uncertain about constructing of learning objectives, the selection of types and forms of assessment. It is recommended to the government and parties related to the development of teacher competencies in learning planning to provide training for the teachers about composing teaching objectives, form and types of assessment aspects so that teachers’ competence and teaching quality can be improved.